2021
DOI: 10.2147/pgpm.s281705
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crucial Genes and Pathways Associated with Atherosclerotic Plaque in Diabetic Patients

Abstract: Background Patients with diabetes have more calcification in atherosclerotic plaque and a higher occurrence of secondary cardiovascular events than patients without diabetes. The objective of this study was to identify crucial genes involved in the development of diabetic atherosclerotic plaque using a bioinformatics approach. Methods Microarray dataset GSE118481 was downloaded from the Gene Expression Omnibus (GEO) database; the dataset included 6 patients with diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Unfortunately, plaque stability cannot be determined histologically despite the increasing number of methods to detect the development of CAPs in T2DM patients. Earlier bioinformatics studies have reported that T2DM alters CAP gene expression (13), but this has not been further confirmed with transcriptomics. Consequently, key biomarkers for T2DM complicated by CAP progression are currently unavailable.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Unfortunately, plaque stability cannot be determined histologically despite the increasing number of methods to detect the development of CAPs in T2DM patients. Earlier bioinformatics studies have reported that T2DM alters CAP gene expression (13), but this has not been further confirmed with transcriptomics. Consequently, key biomarkers for T2DM complicated by CAP progression are currently unavailable.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies have assessed the role of RNAs that are associated with T2DM and CAP progression (75,76). However, only a few studies (13), including this study, have explored the progression of T2DM with CAP using advanced bioinformatic methods. While our results provide useful insights into the role of certain genes and RNAs in the progression of T2DM with CAP, our study also has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 However, the mechanism behind lncRNA in HCC recurrence has not been investigated. Previous studies have indicated that the hsa-miR-24-3p miRNA is associated with many diseases, including atherosclerosis, 36 ischemic chest pain, 37 diabetes, 38 and Parkinson disease. 39 miR-24-3p plays a role in the development of multiple cancers.…”
Section: Discussionmentioning
confidence: 99%